Active integrated antenna with simultaneous transmit and receive - Xuefeng, Qi (2007)
An active antenna with simultaneous transmit and receive function, integrate an active devices onto a printed antenna to improve its performance or combine functions within the antenna itself. Such antenna are of increasing interest, as system designers require more complex functions to be implemented in reduced space. This paper discusses the integration of active antennas by combining both transmit and receive functions into one single antenna. Four main components in the design are circular polarized microstrip patch antenna, rat race coupler, power divider and amplifiers. All the simulations are done using the Agilent ADS. The circular polarized antenna resonates at 2. 4 GHz. Two MESFET amplifiers have been used to transmit and receive the channel separately. The rat race coupler isolates the two channels and a Tee junction power divider is connected the two channels to the input and output port. The channels are of the same frequency. The simulation and measurement results of the microstrip patch antenna for S11 are lower than -10 dB at frequency of 2.4 GHz. The antenna polarization is confirmed as a circular polarized, as can be seen in the radiation pattern from the measured and simulated results. The amplifier biasing circuit is supplied by two power sources; one is the drain voltage (Vds) which is positive and the other is the gate voltage (Vgs), which is negative. After integrating all of the components, the radiation pattern is measured for both transmit and receive. The beamwidth of the antenna is in the range of 60o – 70o for H plane. The radiation pattern for E plane is smaller compared with the H plane. The comparison between the passive and the active integrated antenna shows that the active integrated antenna has 3 dB extra gain compared to the passive antenna for both transmit and receive. The isolation between transmit and receive is between 20 – 25 dB.